Ответы и объяснения

pashapanov2005
pashapanov2005

1) ( х+3 12/17) - 8 9/17= 4 10/17                                                                       х+ 3 12/17-8 9/17=4 10/17                                                                             х=4 10/17 - 3 12/17 + 8 9/17                                                                         х=12 19/17-3 12/17                                                                                         х=9 7/17.

0.0
0 оценок
0 оценок
Оцени!
Оцени!